A low-shrinkage self-compacting slightly expansive concrete and its preparation method
By using composite expansion agents and internal curing agents in self-finished concrete, the problem that self-finished concrete is difficult to self-cure, the low shrinkage and self-curing functions are achieved, and the strength and compactness of the concrete are improved.
Patent Information
- Application Number
- CN202211687585.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2042-12-27
AI Technical Summary
The self-contained concrete structure is dense, and external curing water is difficult to enter the inside of the concrete, resulting in the effect of the expansion agent being less obvious and the concrete is prone to shrinkage cracks.
Low-shrinkage self-finishing micro-expanded concrete is used. By adding composite expansion agents and internal curing agents to the concrete, the composite expansion agents include early and late expansion agents. The internal curing agents contain maltodextrin, nanosilica, humic acid and other components, and act together to achieve self-curing function.
The low shrinkage and self-curing functions of concrete are achieved, which avoids the occurrence of shrinkage cracks and improves the strength and density of concrete.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of self-compacting concrete, and particularly relates to a low-shrinkage self-compacting micro-expansive concrete and a preparation method thereof. Background Technique
[0002] Due to the continuous development of today's construction projects towards the trends of large-scale and multi-functionalization, for some reinforced concrete projects, the internal reinforcement of components is increasing, becoming complex and dense, which leads to an increase in the pouring difficulty of concrete and makes vibration rather difficult; for some thin-walled structures, underground excavation projects, long and slender components, tunnels and some underground projects, etc., there is simply no construction space for vibrating concrete, and it is not easy to insert the vibrating rod, making the construction very difficult and resulting in difficulty in ensuring the quality and durability of concrete. Thus, under this background, self-compacting concrete emerged and met the needs of engineering construction with its high fluidity, thus achieving rapid development.
[0003] CN202010672505.8 discloses a high-strength high-throw self-compacting micro-expansive concrete and a preparation method thereof. Based on the mix proportion of the original high-throw self-compacting concrete, by introducing a tri-expansion-source composite expansive agent, the coordinated development with the strength development and shrinkage deformation of concrete is achieved, obtaining good expansion performance. At the same time, a suitable water-binder ratio and sand ratio are selected to ensure the workability and strength requirements of the obtained high-strength high-throw self-compacting micro-expansive concrete, and the problems existing in the traditional high-throw self-compacting concrete in terms of bleeding segregation and passing ability of the mixture are solved. However, the self-compacting concrete structure is dense, and it is difficult for external curing water to enter the interior of the concrete, failing to achieve the due curing effect, the compensating shrinkage effect of the expansive agent is not obvious, and shrinkage cracks are likely to appear in the concrete structure.
[0004] CN201810190165.8 discloses a low-shrinkage ultra-high-performance concrete doped with SAP. After the water-absorbed SAP is added to the ultra-high-performance concrete, when the internal water in the concrete is consumed by hydration, SAP can release water to enable the unhydrated cementitious materials to continue to hydrate, while reducing the shrinkage problem caused by self-drying. However, the addition of the SAP gel will increase the actual water-binder ratio, and holes will be left after the SAP releases water, resulting in a reduction in the concrete strength.
[0005] CN201910310026.9 discloses a method for preparing concrete with functions of reinforcement, internal curing and compensated shrinkage. A special internal curing agent is prepared by mixing an internal curing agent and an organic early strength component. The added special internal curing agent has the characteristics of high water absorption, high water retention and controllable water release, provides continuous and effective early internal curing effect for concrete, reduces the risk of early shrinkage cracking of concrete, and solves the problem that the strength of concrete is reduced due to internal curing and compensated shrinkage of current concrete. However, the compounding of an early strength agent and an internal curing agent will shorten the setting time of concrete, increase the loss of fluidity of concrete and reduce the operable time. Summary of the Invention
[0006] The purpose of the present invention is to provide a low-shrinkage self-compacting micro-expansive concrete and a preparation method thereof. This concrete not only has excellent workability, pumpability, high strength and low shrinkage, but also can realize the self-curing function, and solves the problem that it is difficult to cure ordinary self-compacting concrete, resulting in an unclear effect of the expansive agent.
[0007] To achieve the above purpose, the present invention provides the following technical solutions:
[0008] A low-shrinkage self-compacting micro-expansive concrete, by weight, comprises the following components: 270-330 parts of cement, 80-120 parts of fly ash, 30-70 parts of slag powder, 10-50 parts of compound expansive agent, 700-900 parts of sand, 900-1100 parts of stone, 7-11 parts of water reducing agent, 0.1-2 parts of internal curing agent, 0.5-1 part of fiber, 140-160 parts of water; wherein:
[0009] The compound expansive agent includes an early-stage expansive agent and a late-stage expansive agent;
[0010] In the internal curing agent, by weight, it includes 5-25 parts of maltodextrin, 1-10 parts of filler, 5-15 parts of macromolecular organic matter, 5-30 parts of ionic monomer, 5-30 parts of non-ionic monomer, 0.01-1 part of crosslinking agent, 0.001-0.1 part of initiator, 1-10 parts of neutralizing reagent, 60-90 parts of deionized water;
[0011] In the internal curing agent, the filler is nano-silica, and the macromolecular organic matter is humic acid.
[0012] According to the above scheme, in the internal curing agent, the ionic monomer is 2-acrylamide-2-methylpropanesulfonic acid, the non-ionic monomer is acrylamide, the crosslinking agent is N,N'-methylenebisacrylamide, the initiator is potassium persulfate, and the neutralizing reagent is sodium hydroxide.
[0013] According to the above scheme, the preparation of the internal curing agent includes the following steps:
[0014] 1) Add maltodextrin to deionized water and stir evenly. Gelatinize it in a constant temperature water bath at 50 - 90 °C. Maintain the above temperature, add fillers to the gelatinized solution and stir for 10 - 30 minutes to obtain solution A;
[0015] 2) Dissolve ionic monomers in deionized water and add neutralizing reagents to prepare a monomer solution with a neutralization degree of 65 - 75%. Sequentially add macromolecular organic substances, non-ionic monomers, and cross-linking agents to the above monomer solution and mix evenly to obtain solution B;
[0016] 3) Dissolve initiators in deionized water to prepare initiator solution C;
[0017] 4) Then slowly add B and C to A respectively, control the total dropping time within 30 - 90 minutes, stir evenly and keep the temperature for reaction for 2 - 5 hours to obtain a gel. Dry and crush the gel to obtain an internal curing agent with a particle size of 100 - 150 μm.
[0018] According to the above scheme, the cement is 52.5 grade ordinary Portland cement, the residue on 80 μm sieve is 2.7%, and the 28d compressive strength > 60 MPa.
[0019] According to the above scheme, the fly ash is Class I fly ash, the water demand ratio is 94%, and the Blaine specific surface area ≥ 400 m 2 / kg; the slag powder is S95 grade slag powder, the 28d activity index ≥ 95%, and the Blaine specific surface area ≥ 700 m 2 / kg.
[0020] According to the above scheme, in the composite expansive agent, the mass ratio of the early-stage expansive agent to the late-stage expansive agent is 1:(1 - 3).
[0021] According to the above scheme, the early-stage expansive agent is at least one of azo compounds, sulfonylhydrazide compounds, and nitroso compounds; the late-stage expansive agent is at least one of calcium oxide type, calcium sulfoaluminate type, magnesium oxide type, and calcium sulfoaluminate - calcium oxide type.
[0022] According to the above scheme, the sand is river sand, the fineness modulus is 2.46, and the mud content is 1.5%; the stone is ordinary crushed stone, with a continuous gradation of 5 - 20 mm, the content of needle-like and flaky particles is 2.74%, and the crushing value is 7.1%.
[0023] According to the above scheme, the water reducer is a polycarboxylate superplasticizer, the solid content ≥ 25%, and the water reduction rate ≥ 30%.
[0024] According to the above scheme, the fibers include carbon fibers and polypropylene fibers; among them, the length of carbon fibers is 6 - 12 mm, the length of polypropylene fibers is 12 - 19 mm; the mass ratio of carbon fibers to polypropylene fibers is (1 - 5):1.
[0025] The present invention also provides a method for preparing low-shrinkage self-compacting and slightly expansive concrete, comprising the following steps:
[0026] First, sand, stones and fibers are dry-mixed and stirred, then part of water is added for wet mixing, then cement, fly ash, slag powder, expansive agent, internal curing agent and water reducer are added for mixing, and finally the remaining water is added and stirred evenly to obtain the low-shrinkage self-compacting and slightly expansive concrete, which can be directly poured or plastered on the formwork without vibration.
[0027] The present invention provides a low-shrinkage self-compacting and slightly expansive concrete, which uses a composite expansive agent supplemented with an internal curing agent, wherein:
[0028] In the composite expansive agent, the combined use of the early-stage expansive agent and the late-stage expansive agent enables the composite expansion component to react and generate expansion in both the early and late stages of hydration, better compensating for the shrinkage of concrete in each period and realizing the coordinated development of concrete strength and shrinkage deformation. However, when the composite expansive agent is used alone, the expansion effect is not obvious due to the difficulty of water entering the interior of the concrete.
[0029] The internal curing agent stores a large amount of water at the initial stage of concrete mixing. It can not only absorb part of the heat generated by the hydration of the cementitious material and inhibit the internal hydration temperature rise of the concrete, but also release free water when the internal humidity is unsaturated, increasing the relative humidity of its surrounding environment. On the one hand, it inhibits the autogenous shrinkage and drying shrinkage of the concrete, and on the other hand, it promotes the continuous hydration of cementitious materials such as cement, especially the expansive agent, enabling the coordinated development of the volume expansion and strength growth of the concrete and ensuring the continuous and stable properties of the concrete in the later stage.
[0030] Meanwhile, in the internal curing agent of the present invention, nano-silica enhances the strength of the internal curing agent and improves its shear resistance in the concrete. Moreover, after the internal curing agent releases water, nano-silica fillers are left, which can refine the pores of the concrete and enhance the density, thereby improving the concrete strength; humic acid is a macromolecular compound, showing a loose structure in aqueous solution and having a certain liquid absorption capacity. There are also a large number of groups in humic acid that can chelate metal ions, capable of complexing metal ions in the paste, reducing their ion concentration, thereby increasing the liquid absorption ratio and enhancing the internal curing effect.
[0031] Fibers are also used in combination in the present invention. They are interspersed in the cement stone and can play the roles of "micro fine steel bars" and "reinforcing bars", having good crack resistance and stress transfer capabilities, which are beneficial to improving the crack resistance and toughness of the concrete. At the same time, cement is used as the main cementitious material, and fly ash and slag powder are used as mineral admixtures. The specific surface area of the admixtures is relatively large, which can form a good particle gradation and close packing system with the cement. Moreover, the secondary hydration of the admixtures in the later stage can reduce the early hydration heat and reduce the pathways for harmful substances to enter the interior of the concrete.
[0032] The beneficial effects of the present invention are as follows:
[0033] 1. The present invention provides a low-shrinkage self-compacting and slightly expanding concrete, which uses cement as the main cementitious material, fly ash and slag powder as mineral admixtures, is combined with fibers, and synergistically uses a composite expansive agent and an internal curing agent; the obtained concrete has low early hydration heat, and high density and toughness in the later stage, and can effectively prevent the generation of cracks from the source.
[0034] 2. The present invention utilizes the water absorption and release function of the internal curing agent, which not only reduces the hydration heat and shrinkage of the concrete, but also provides moisture for the admixtures and the expansive agent, promotes their hydration, and fully exerts the expansion efficiency of the expansive agent; at the same time, nano-silica filler and humic acid are added on the basis of the preparation of the conventional internal curing agent, which enhances the anti-shear ability and liquid absorption ability of the internal curing agent, not only improves its internal curing effect, but also weakens the problem of the reduction of the concrete strength caused by the internal curing.
[0035] 3. The present invention provides a preparation method of a low-shrinkage self-compacting and slightly expanding concrete. First, sand, stones and fibers are dry-mixed and stirred, then part of the water is added for wet mixing, which is beneficial to the uniform dispersion of the fibers, and finally other raw materials are added. The preparation method is simple, the construction is convenient, no vibration is required, and the raw materials are widely sourced, which is beneficial to industrial application. Specific Embodiments
[0036] To better understand the content of the present invention, the following examples are further described, but the content of the present invention is not limited to the following examples.
[0037] In the following examples, the cement is Conch 52.5-grade ordinary Portland cement, the fly ash is Class I fly ash from a certain power plant in Yangluo, the slag powder is S95-grade slag powder from Wuxin New Building Materials Co., Ltd., the composite expansive agent is composed of azodicarbonamide and calcium sulfoaluminate-calcium oxide in a ratio of 3:7, the sand is Zunhua river sand, the stones are Zunhua crushed stones, the water reducer is a high-performance water reducer from Jiangsu Sobute New Materials Co., Ltd., the internal curing agent is a self-made material, the fibers are a mixture of carbon fiber and polypropylene fiber in a ratio of 2:1, and the water is tap water.
[0038] Among the fibers, the length of the carbon fiber is 6-12 mm, and the length of the polypropylene fiber is 12-19 mm.
[0039] In the internal curing agent, by weight, it includes 15 parts of maltodextrin, 5 parts of filler nano-silica, 10 parts of macromolecular organic matter humic acid, 15 parts of ionic monomer 2-acrylamide-2-methylpropanesulfonic acid, 15 parts of non-ionic monomer acrylamide, 0.1 part of cross-linking agent N,N'-methylenebisacrylamide, 0.01 part of initiator potassium persulfate, 5 parts of neutralizing reagent sodium hydroxide, and 75 parts of deionized water;
[0040] Among them, the internal curing agent is prepared through the following steps:
[0041] 1) Add maltodextrin to deionized water and stir evenly. Gelatinize it in a constant temperature water bath at 70 °C. Maintain the above temperature, add nano-silica to the gelatinized solution and stir for 20 minutes to obtain solution A;
[0042] 2) Dissolve 2-acrylamido-2-methylpropanesulfonic acid in deionized water and add sodium hydroxide to prepare a monomer solution with a neutralization degree of 70%. Add humic acid, acrylamide, and N,N'-methylenebisacrylamide to the above monomer solution in sequence and mix evenly to obtain solution B;
[0043] 3) Dissolve potassium persulfate in deionized water to prepare potassium persulfate solution C;
[0044] 4) Then slowly add B and C to A respectively, control the total dropping time within 60 minutes, stir evenly and keep the reaction at a constant temperature for 4 hours to obtain a gel. Dry and crush the gel to obtain an internal curing agent with a particle size of 100 - 150 μm.
[0045] Example 1
[0046] A low-shrinkage self-compacting slightly expanding concrete, comprising the following components in parts by weight: 300 parts of cement, 100 parts of fly ash, 50 parts of slag powder, 30 parts of composite expansive agent, 807 parts of sand, 1070 parts of stone, 9.12 parts of water reducing agent, 0.48 part of internal curing agent, 0.8 part of fiber, and 147 parts of water.
[0047] A preparation method of a low-shrinkage self-compacting slightly expanding concrete, comprising the following steps: First, dry-mix and stir sand, stone, and fiber, then add part of the water for wet mixing, then add cement, fly ash, slag powder, composite expansive agent, internal curing agent, and water reducing agent for mixing, and finally add the remaining water and stir evenly to obtain the low-shrinkage self-compacting slightly expanding concrete.
[0048] Example 2
[0049] A low-shrinkage self-compacting slightly expanding concrete, comprising the following components in parts by weight: 300 parts of cement, 100 parts of fly ash, 50 parts of slag powder, 30 parts of composite expansive agent, 807 parts of sand, 1070 parts of stone, 9.12 parts of water reducing agent, 0.96 part of internal curing agent, 0.8 part of fiber, and 155 parts of water.
[0050] A preparation method of a low-shrinkage self-compacting slightly expanding concrete, comprising the following steps: First, dry-mix and stir sand, stone, and fiber, then add part of the water for wet mixing, then add cement, fly ash, slag powder, composite expansive agent, internal curing agent, and water reducing agent for mixing, and finally add the remaining water and stir evenly to obtain the low-shrinkage self-compacting slightly expanding concrete.
[0051] Example 3
[0052] A low-shrinkage self-compacting slightly expanding concrete, comprising the following components in parts by weight: 300 parts of cement, 100 parts of fly ash, 50 parts of slag powder, 30 parts of composite expansive agent, 807 parts of sand, 1070 parts of stone, 9.12 parts of water reducing agent, 1.44 parts of internal curing agent, 0.8 part of fiber, and 155 parts of water.
[0053] A preparation method of the low-shrinkage self-compacting slightly expanding concrete comprises the following steps: first, dry-mix and stir the sand, stone, and fiber, then add part of the water for wet mixing, then add the cement, fly ash, slag powder, composite expansive agent, internal curing agent, and water reducing agent for mixing, and finally add the remaining water and stir evenly to obtain the low-shrinkage self-compacting slightly expanding concrete.
[0054] Control Example 1
[0055] A self-compacting concrete, comprising the following components in parts by weight: 300 parts of cement, 120 parts of fly ash, 60 parts of slag powder, 0 part of composite expansive agent, 807 parts of sand, 1070 parts of stone, 8.64 parts of water reducing agent, 0 part of internal curing agent, 0.8 part of fiber, and 140 parts of water.
[0056] A preparation method of the self-compacting concrete comprises the following steps: first, dry-mix and stir the sand, stone, and fiber, then add part of the water for wet mixing, then add the cement, fly ash, slag powder, and water reducing agent for mixing, and finally add the remaining water and stir evenly to obtain the self-compacting concrete.
[0057] Control Example 2
[0058] A self-compacting slightly expanding concrete, comprising the following components in parts by weight: 300 parts of cement, 100 parts of fly ash, 50 parts of slag powder, 30 parts of composite expansive agent, 807 parts of sand, 1070 parts of stone, 8.64 parts of water reducing agent, 0 part of internal curing agent, 0.8 part of fiber, and 140 parts of water.
[0059] A preparation method of the self-compacting slightly expanding concrete comprises the following steps: first, dry-mix and stir the sand, stone, and fiber, then add part of the water for wet mixing, then add the cement, fly ash, slag powder, composite expansive agent, and water reducing agent for mixing, and finally add the remaining water and stir evenly to obtain the self-compacting slightly expanding concrete.
[0060] Control Example 3
[0061] A low-shrinkage self-compacting slightly expanding concrete, comprising the following components in parts by weight: 300 parts of cement, 100 parts of fly ash, 50 parts of slag powder, 30 parts of expansive agent, 807 parts of sand, 1070 parts of stone, 9.12 parts of water reducing agent, 0.48 part of commercially available superabsorbent resin, 0.8 part of fiber, and 147 parts of water.
[0062] A preparation method of self-compacting slightly expansive concrete comprises the following steps: firstly, dry-mix and stir sand, stones and fibers, then add partial water for wet mixing, next add cement, fly ash, blast furnace slag, expansive agent and water reducer for mixing, and finally add the remaining water and stir evenly to obtain self-compacting slightly expansive concrete.
[0063] The performance test results of the self-compacting concrete prepared in each example and comparative example are shown in the following table:
[0064] Table 1 Concrete performance test results
[0065] Test items Comparative example 1 Comparative example 2 Comparative example 3 Example 1 Example 2 Example 3 Slump / mm 260 255 250 245 235 235 Spread / mm 690 675 655 650 615 560 Compressive strength (3d) / MPa 40.2 43.7 39.2 41.2 39.5 37.6 Compressive strength (7d) / MPa 53.3 56.7 49.1 53.2 49.7 46.3 Compressive strength (28d) / MPa 71.2 71.9 68.6 71.3 69.3 63.7 Compressive strength (60d) / MPa 77.5 78.3 75.2 79.9 76.6 68.3 <![CDATA[60d drying shrinkage rate / (×10 -6 )]]> 255 210 189 165 100 60
[0066] It can be seen from the test results in Table 1 that after adding the expansive agent, the strength of the concrete at each age increases and the dry shrinkage rate at 60 d decreases; and the addition of the internal curing agent further reduces the dry shrinkage rate of the concrete, indicating that the combined use of the internal curing agent and the expansive agent has a significant effect on inhibiting the shrinkage of the concrete. And compared with the commercially available internal curing agent in Comparative Example 3, the examples of the present invention have lower dry shrinkage at the same strength or even higher strength, indicating that the optimized self-made internal curing agent of the present invention has a significant effect. At the same time, when the dosage of the self-made internal curing agent is small, such as in Example 1, the self-made internal curing agent makes the 28-day strength of the concrete basically reach the level of Comparative Example 2, and the 60-day strength is greater than that of Comparative Example 2, indicating that the self-made internal curing is also beneficial to the strength of the concrete at an appropriate dosage.
[0067] The above embodiments are only the preferred embodiments of the present invention. It should be noted that based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
Claims
1. A low-shrinkage self-compacting slightly expanding concrete, characterized in that, by weight, it comprises the following components: 270 - 330 parts of cement, 80 - 120 parts of fly ash, 30 - 70 parts of slag powder, 10 - 50 parts of composite expansion agent, 700 - 900 parts of sand, 900 - 1100 parts of stone, 7 - 11 parts of water reducing agent, 0.1 - 2 parts of internal curing agent, 0.5 - 1 part of fiber, and 140 - 160 parts of water; wherein: the composite expansion agent includes an early expansion agent and a late expansion agent; in the internal curing agent, by weight, it includes 5 - 25 parts of maltodextrin, 1 - 10 parts of filler, 5 - 15 parts of macromolecular organic matter, 5 - 30 parts of ionic monomer, 5 - 30 parts of non-ionic monomer, 0.01 - 1 part of cross-linking agent, 0.001 - 0.1 part of initiator, 1 - 10 parts of neutralizing reagent, and 60 - 90 parts of deionized water; in the internal curing agent, the filler is nano-silica, the macromolecular organic matter is humic acid, the ionic monomer is 2-acrylamide-2-methylpropanesulfonic acid, the non-ionic monomer is acrylamide, the cross-linking agent is N,N'-methylenebisacrylamide, the initiator is potassium persulfate, and the neutralizing reagent is sodium hydroxide.
2. The low-shrinkage self-compacting slightly expanding concrete according to claim 1, characterized in that, the preparation of the internal curing agent includes the following steps: 1) Add maltodextrin to deionized water and stir evenly, gelatinize in a constant temperature water bath at 50 - 90 °C, maintain the above temperature, add the filler to the gelatinized solution and stir for 10 - 30 minutes to obtain solution A; 2) Dissolve the ionic monomer in deionized water and add the neutralizing reagent to prepare a monomer solution with a neutralization degree of 65 - 75%, and successively add the macromolecular organic matter, non-ionic monomer, and cross-linking agent to the above monomer solution and mix evenly to obtain solution B; 3) Dissolve the initiator in deionized water to obtain initiator solution C; 4) Then slowly drop B and C into A respectively, control the total dropping time within 30 - 90 minutes, stir evenly and keep the temperature for reaction for 2 - 5 hours to obtain a gel, dry and crush the gel to obtain an internal curing agent with a particle size of 100 - 150 μm.
3. The low-shrinkage self-compacting slightly expanding concrete according to claim 1, characterized in that, The cement is 52.5 grade ordinary Portland cement, with a residue on 80μm sieve of 2.7% and a 28-day compressive strength > 60 MPa; the fly ash is Class I fly ash, with a water demand ratio of 94% and a Blaine specific surface area ≥ 400 m 2 / kg; the blast furnace slag powder is S95 grade blast furnace slag powder, with a 28-day activity index ≥ 95% and a Blaine specific surface area ≥ 700 m 2 / kg.
4. The low-shrinkage self-compacting slightly expanding concrete according to claim 1, characterized in that, in the composite expansion agent, the mass ratio of the early expansion agent to the late expansion agent is 1:(1 - 3).
5. The low-shrinkage self-compacting slightly expanding concrete according to claim 1, characterized in that, the early expansion agent is at least one of azo compounds, sulfonyl hydrazide compounds, and nitroso compounds; the late expansion agent is at least one of calcium oxide type, calcium sulfoaluminate type, magnesium oxide type, and calcium sulfoaluminate-calcium oxide type.
6. The low-shrinkage self-compacting slightly expanding concrete according to claim 1, characterized in that, the sand is river sand with a fineness modulus of 2.46 and a mud content of 1.5%; the stone is ordinary crushed stone with a continuous gradation of 5 - 20 mm, a flake and needle content of 2.74%, and a crushing value of 7.1%.
7. The low-shrinkage self-compacting slightly expanding concrete according to claim 1, characterized in that, The water reducing agent is a polycarboxylate high-performance water reducing agent with a solid content of ≥ 25% and a water reducing rate of ≥ 30%.
8. The low shrinkage self-compacting slightly expansive concrete according to claim 1, characterized in that the fibers include carbon fibers and polypropylene fibers; wherein the length of the carbon fibers is 6 - 12 mm, the length of the polypropylene fibers is 12 - 19 mm; and the mass ratio of the carbon fibers to the polypropylene fibers is (1 - 5):
1.
9. A method for preparing the low shrinkage self-compacting slightly expansive concrete according to any one of claims 1 - 8, characterized in that it comprises the following steps: First, dry mix and stir the sand, stones and fibers, then add part of the water for wet mixing, then add cement, fly ash, blast furnace slag powder, composite expansive agent, internal curing agent and water reducing agent for mixing, and finally add the remaining water and stir evenly to obtain the low shrinkage self-compacting slightly expansive concrete, which can be directly poured or molded and leveled without vibration.
Citation Information
Patent Citations
SAP (Super Absorbent Polymer)-doped low-contraction ultrahigh-performance concrete
CN108358556A
Preparation method of concrete with functions of reinforcing, internal curing and shrinkage compensating
CN109987899A
A high-strength, high-polish, self-compacting, micro-expansion concrete and its preparation method
CN111763050B
C30 self-compaction microexpanded concrete-filled steel tube and preparation method thereof
CN105084836A
Micro-expansion high-performance low-gas content self-compacting concrete
CN108358562A